Melanotic neuroectodermal tumour of infancy. (23rd November 2010) - Pattanayak, Sweta; Ray, Jay Gopal; Richa,; Mukherjee, Sanjit; Mandal, Chitra; Chaudhuri, Keya
Abstract : Melanotic neuroectodermal tumour of infancy (MNTI) is a rare benign tumour of neural crest origin that was first described by Krompecher in 1918.1 It is predominantly found in infancy, with about 92% of cases below the age of 12 months and 82% below the age of 6 months. The predominant site of origin is in the premaxilla though it is reported at other sites also including the skull, the mandible, the epididymis and the brain.2 The lesions often have areas of bluish discolouration on the surface and are characterised by displacement of the involved tooth bud and local aggressiveness. The present report deals with two cases of MNTI, a 5-month-old baby girl and a 6-month-old baby boy who reported to the Department of Oral and Maxillofacial Pathology, Dr R Ahmed Dental College and Hospital, Kolkata, India. The clinical, radiological, histological and immunohistochemical findings, confirmed the diagnosis of MNTI. Flow cytometry was performed to analyse aneuploidy. The tumours were treated surgically with no history of recurrence to date.